Edukasi Penyehatan Makanan Bagi Pengelola dan Penjamah Makanan pada Rumah Makan di Kelurahan Babau Kecamatan Kupang Timur Kabupaten Kupang - Byantarsih Widyaningrum; Erika Maria Resi; Ferry WF Waangsir (Health Care : Journal of Community Service, 2025)
Food handling in restaurants must pay attention to the safety, health, and quality standards that have been set in order to obtain quality food products and minimize contamination of pathogenic bacteria in food that can cause foodborne diseases. The primary target of this activity is food managers and handlers at restaurants in Babau Village, Kupang Regency. The service method is to conduct location surveys, approaches and location permits to the Babau Village Government, socialization of activities, counseling, practices of implementing Personal Protective Equipment, provision of Personal Protective Equipment, as well as monitoring and evaluation of activities. The result of this activity is an increase in the knowledge of food managers and handlers through information about individual hygiene, equipment sanitation, kitchen sanitation, hygiene, sanitation of food and processed food to food managers and handlers, and participants can practice the correct application of personal protective equipment use.